2010
DOI: 10.1097/inf.0b013e3181b92109
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Methicillin-Susceptible Staphylococcus aureus in a University Medical Center Day Care Facility

Abstract: The prevalence of MSSA colonization in children and care providers in a university medical center child care center is similar to that of the general population. Children colonized with MSSA tended to be older and to have received fewer courses of antibiotics than children who did not have MSSA. The relatedness of many of the isolates indicates that transmission of MSSA occurred at this child care center.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…ST8 has previously been found in CA-MRSA isolates collected globally and in the United States, and multiple studies have reported finding both CA-MRSA and HA-MRSA strains in daycare centers. 7,9,10,34,35 These findings, coupled with the fact that a traditionally livestock-associated strain was identified in an employee, suggest that daycare centers could serve as community "mixing bowls" in which HA-, CA-, and livestock-associated S aureus strains exchange genetic information. Daycare facilities, along with other community settings such as gyms and schools, may serve as important transmission sites for S aureus and for acquisition of the organism.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…ST8 has previously been found in CA-MRSA isolates collected globally and in the United States, and multiple studies have reported finding both CA-MRSA and HA-MRSA strains in daycare centers. 7,9,10,34,35 These findings, coupled with the fact that a traditionally livestock-associated strain was identified in an employee, suggest that daycare centers could serve as community "mixing bowls" in which HA-, CA-, and livestock-associated S aureus strains exchange genetic information. Daycare facilities, along with other community settings such as gyms and schools, may serve as important transmission sites for S aureus and for acquisition of the organism.…”
Section: Discussionmentioning
confidence: 87%
“…Although a study conducted at 2 academic health center daycare facilities in Florida did not find MRSA on surfaces, fingerprint patterns of S aureus isolated from a facility in Texas showed indistinguishable clones from children, employees, and surfaces, illustrating the potential for inanimate objects to contribute to transmission. 7,32 It is important to gather more information about the number and types of surfaces that are contaminated in daycare facilities, otherwise efforts to eliminate a pathogen from a facility via decolonization of children and workers may prove futile. Data on which environmental surfaces most often harbor pathogens could help employees target problem surfaces with hygiene measures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The three patients who were colonized had CD4 counts > 200/uL, undetectable viral loads and were not receiving any prophylaxis. The colonization rate of 22% found for the control group reflects that of the general population [1,19] and likely represents the current rate of colonization in this age group in our community.…”
Section: Discussionmentioning
confidence: 55%